Genomic analysis of two Acinetobacter baumannii strains belonging to two different sequence types (ST172 and ST25). (December 2020) - Montaña, Sabrina; Vilacoba, Elisabet; Fernandez, Jennifer S.; Traglia, German M.; Sucari, Adriana; Pennini, Magdalena; Iriarte, Andres; Centron, Daniela; Melano, Roberto G.; Ramírez, María Soledad
Highlights: WGS analysis and comparison of two A. baumannii strains belonging to emergent ST25 and sporadic ST172. Molecular characterisation revealed differences in the content of antibiotic resistance genes and mobile genetic elements. Differences at the genomic level can in part explain the success of ST25 in comparison with ST172. Characterisation of a previously uncharacterised ST (ST172) and further characterisation of the widely studied ST25. Abstract: Objectives: Acinetobacter baumannii is an opportunistic nosocomial pathogen that is the main focus of attention in clinical settings owing to its intrinsic ability to persist in the hospital environment and its capacity to acquire determinants of resistance and virulence. Here we present the genomic sequencing, molecular characterisation and genomic comparison of two A. baumannii strains belonging to two different sequence types (STs), one sporadic and one widely distributed in our region. Methods: Whole-genome sequencing (WGS) of Ab42 and Ab376 was performed using Illumina MiSeq-I and the genomes were assembled with SPAdes. ARG-ANNOT, CARD-RGI, ISfinder, PHAST, PlasmidFinder, plasmidSPAdes and IslandViewer were used to analyse both genomes. Results: Genome analysis revealed that Ab42 belongs to ST172, an uncommon ST, whilst Ab376 belongs to ST25, a widely distributed ST. Molecular characterisation showed the presence of two antibiotic resistance genes in Ab42 and nine in Ab376. No insertion sequences were detected in Ab42, however 22 were detected in Ab376. Moreover, two prophages were found in Ab42 and three in Ab376. In addition, a CRISPR-cas type I-Fb and two plasmids, one of which harboured an AbGRI1-like island, were found in Ab376. Conclusions: We present WGS analysis of two A. baumannii strains belonging to two different STs. These findings allowed us to characterise a previously undescribed ST (ST172) and provide new insights to the widely studied ST25.